Preparation of Indigo Paste for Natural Dyeing of Timor Woven Fabric in Amol Village, North Central Timor Regency - Risna Erni Yati Adu; Marselina Theresia Djue Tea; Gebhardus Djugian Gelyaman; Jefry Presson (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2022)
The lack of knowledge and skills of the weaver community in Amol Village, North Central Timor Regency to prepare natural dye from natural resources that are difficult to be found in dry season is the main reason to conduct this service activity. This training was aimed to improve the knowledge and skills of the weaver group and providing them indigo paste as a natural color stock that can be stored and used during dry season. Service activities were carried out through 2 steps, namely counseling and training, which begins with a demonstration by service team and then continues with independent practice while being accompanied by the team. The knowledge of the weaver group to extract natural dyes from natural resources has been improved, as evidenced by the evaluation results. Members of the weaver group became more skilled in preparing indigo paste from Indigofera tinctoria leaves. At the end of the activity, indigo paste products were obtained which were applied to Timor woven fabric.